Anhydrite and Gypsum Compositions Modified with Ultrafine Man-Made Admixtures. (2015) - Yakovlev, Grigory; Polyanskikh, Irina; Fedorova, Galina; Gordina, Anastasiia; Buryanov, Aleksandr
Abstract: The influence of technogenic ultrafine additives on structure and properties of binders based on calcium sulfate has been studied. The study of physical and mechanical properties of gypsum compositions modified with metallurgical dust has showed an increase in ultimate compressive strength up to 30%, ultimate bending strength – 15%, the value of water resistance of the binder did not change. 1% of metallurgical dust being added to natural anhydrite, there is a significant increase of the strength of the composition by 40%, and the water resistance of the material decreases slightly. The conducted X-ray analysis does not show the presence of any new products of hydration and intensification of hydration of calcium sulfate dehydrate. At the same time, the conducted studies of the structure of the compositions confirm significant changes in the morphology of new formations. Thus, adding ultrafine additives to natural anhydrite and gypsum leads to the formation of a dense matrix of the increased strength.